A Peer-to-Peer Approach to Implementation of a Chronic Disease Management Program - Sibbald, Shannon L.; Paciocco, Stefan; Huizhu Chen, Lucy; Joshi, Atharv; Ferrone, Madonna; Licskai, Christopher (Journal of Research in Interprofessional Practice and Education, 2022)
Background: Peer-to-peer (P2P) learning occurs when individuals from similar social groups or professions help each other to learn new knowledge skills or problem solving. Peer-to-peer learning is used across many disciplines but has not been widely studied in primary care or chronic disease management. This study explored the use of an interprofessional P2P approach to support the implementation of a chronic disease management program in primary care for patients with chronic obstructive pulmonary disease (COPD), known as Best Care COPD (BCC).Methods and findings: A single descriptive case study design was used to explore P2P learning implementation approach. Focus groups and key informant interviews were held with providers involved in implementation (n = 26). Three key components of the P2P approach were identified: 1) an interprofessional team, 2) iterative peer-led training, and 3) continuous peer connection. Three recommendations are provided to support future P2P efforts: 1) enlist a champion in each profession, 2) build a P2P community, and 3) implement succession planning.Conclusion: This article provides an empirical example of the use of a P2P approach in primary care program implementation. The results will inform the future implementation of programs for chronic disease management as well as the continued sustainability of the BCC program.